High genetic connectivity among large populations of Pteronotus gymnonotus in bat caves in Brazil and its implications for conservation - Ito, Fernanda; Lilley, Thomas; Twort, Victoria G.; Bernard, Enrico (Frontiers in Ecology and Evolution, 2022)
Bat caves in the Neotropical region shelter exceptional bat populations (some > 100,000 individuals). Their populations have a wide role in ecological interactions, are vulnerable due to their restriction to caves, and have a disproportionate conservation value. Current knowledge on bat caves in Brazil is still small. However, the systematic monitoring of some bat caves in Northeastern Brazil shows they experience strong population fluctuations in short periods of time, suggesting large scale bat movements between roosts and a much broader use of the landscape than previously considered. A spatio-temporal reproductive connectivity between distant populations would change our understanding of roost use among bat species in Brazil, and important gaps on the knowledge about large-distance bat movements in the country would be filled. Here, we used ddRADseq data to analyze the genetic structure of Pteronotus gymnonotus across nine bat caves along 700 km. Our results indicate lack of a clear geographic structure with gene flow among all of the analyzed caves, confirming that large numbers of P. gymnonotus use a network of geographically segregated bat caves hundreds of kilometers away. Facing strong anthropogenic impacts and an underrepresentation of caves in conservation action plans worldwide, the genetic connectivity here demonstrated confirms that bat caves are priority sites for bat and speleological conservation in Brazil and elsewhere. Moreover, our results are a warning call: applied aspects of the environmental licensing of the mining sector and its impact must be reviewed, not just in Brazil, but wherever this licensing affects caves with exceptional bat populations.